2007
DOI: 10.1007/s10800-007-9463-5
|View full text |Cite
|
Sign up to set email alerts
|

Current and voltage distributions in a tubular solid oxide fuel cell (SOFC)

Abstract: International audienceOne of the major obstacles to improving electrochemical performance of SOFCs is the limitation with respect to current collecting. The aim of this study is to examine these limitations on the basis of a model of a single cell of tubular SOFC. The simulation results allow us to understand and analyze the effects of ionic and electronic ohmic drops on cell performance. This paper describes a model using the CFD-Ace software package to simulate the behaviour of a tubular SOFC. Modelling is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…8, as higher local current densities would cause higher heating due to the increased irreversible losses associated with the overpotentials, charged species flow and reaction entropies. Such temperature variations across the PEN of micro-tubular SOFCs have also been reported by other studies [20,33,57] with similar magnitudes of (10-15 K) temperature variations being reported across the PEN for similar lengths at similar polarisation [33]. Fig.…”
Section: Flow Behaviour and Spatial Distributions Of Temperature Reasupporting
confidence: 87%
See 1 more Smart Citation
“…8, as higher local current densities would cause higher heating due to the increased irreversible losses associated with the overpotentials, charged species flow and reaction entropies. Such temperature variations across the PEN of micro-tubular SOFCs have also been reported by other studies [20,33,57] with similar magnitudes of (10-15 K) temperature variations being reported across the PEN for similar lengths at similar polarisation [33]. Fig.…”
Section: Flow Behaviour and Spatial Distributions Of Temperature Reasupporting
confidence: 87%
“…A finite volume 3-D model has been reported [20] of a tubular SOFC with inner diameter 5 mm and porous gas diffusion electrodes, in which spatially distributed current generation occurred. SOFC performance was predicted to increase with cathode conductivities, whereas low electronic conductivities caused strong potential gradients around the circumference of the cell when contact was made over a short arc.…”
Section: Introductionmentioning
confidence: 99%
“…A quite good agreement between experimental and simulated data was obtained with these kinetic electrochemical parameters [22]. The velocity constants according to [7,13,14] are presented in the Table 3.…”
Section: Simulation Parameterssupporting
confidence: 64%
“…Solid oxide full cells (SOFC) represent an advanced technology for clean, high efficient and reliable energy conversion, which has attracted more and more attentions worldwide [1][2][3]. Tubular SOFC have many advantages such as the ease of sealing, the ability to endure the thermal stress caused by rapid heating [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Tubular SOFC have many advantages such as the ease of sealing, the ability to endure the thermal stress caused by rapid heating [3][4][5][6]. However, interconnector still remains to be a main challenge holding back single fuel cells from being compiled into stacks [7,8].…”
Section: Introductionmentioning
confidence: 99%